Risk of cardiovascular disease in rheumatoid arthritis patients - A P Utari; Rudy Hidayat; Bambang Setiyohadi (Indonesian Journal of Rheumatology, 2011)
Despite rheumatoid arthritis (RA) therapy development has been in advance level today, its mortality remains increasing in general population. The mortality is mainly caused by early-manifested atherosclerosis and other cardiovascular complications. Available evidences showthis condition appears in early stage of the disease. Thus, early detection and management of cardiovascular risk, followed by control of these factors are necessaryto reduce morbidity and mortality of RA patients